2018
DOI: 10.30848/pjb2019-1(30)
|View full text |Cite
|
Sign up to set email alerts
|

Drought affects aquaporins gene expression in important pulse legume chickpea (Cicer arietinum L.)

Abstract: Aquaporins (AQPs) mediate cross membrane transport of water and other solutes in plants. AQPs also enhance plant performance under environmental stresses including water shortage. Chickpea (Cicer arietinum L.) is the most important pulse legume for the people of semi-arid tropics. To understand the evolutionary relationships and role of AQPs in drought tolerance in chickpea, the current study involves an evolutionary analysis coupled with expression analysis and promoter analysis of selected AQPs. A total of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…These gene families have been identified in other legume crops, such as groundnut (Shivaraj et al, 2019). In a subsequent study, RT-PCR based expression analysis revealed that the PIP2; 2 and NIP6; 3 genes expressed in roots increase drought tolerance in chickpea, while contrary role has been observed for other genes SIP1; 1 and PIP2; 3 as their expression increased the sensitivity to drought (Azeem et al, 2019).…”
Section: Transcriptomics and Elucidation Of Network Genes Controlling Root Traitsmentioning
confidence: 94%
See 2 more Smart Citations
“…These gene families have been identified in other legume crops, such as groundnut (Shivaraj et al, 2019). In a subsequent study, RT-PCR based expression analysis revealed that the PIP2; 2 and NIP6; 3 genes expressed in roots increase drought tolerance in chickpea, while contrary role has been observed for other genes SIP1; 1 and PIP2; 3 as their expression increased the sensitivity to drought (Azeem et al, 2019).…”
Section: Transcriptomics and Elucidation Of Network Genes Controlling Root Traitsmentioning
confidence: 94%
“…These gene families have been identified in other legume crops, such as groundnut (Shivaraj et al, 2019). In a subsequent study, RT‐PCR based expression analysis revealed that the PIP2; 2 and NIP6; 3 genes expressed in roots increase drought tolerance in chickpea, while contrary role has been observed for other genes SIP1; 1 and PIP2; 3 as their expression increased the sensitivity to drought (Azeem et al, 2019). Similarly, candidate genes associated with different functional groups, including molecular, cellular, and biological processes, expressed under drought conditions have been identified in lentil through transcriptome analysis (Singh et al, 2017).…”
Section: Root Characteristics For Improving Water Productivitymentioning
confidence: 96%
See 1 more Smart Citation
“…The prime limiting factors for realizing the higher yield of this crop can be attributed to lack of genetic variability, indeterminate growth habit, canopy architecture, poor harvest index, cultivation in marginal lands and susceptibility to pests and diseases (Azeem et. al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A KUP member in plants was first identified in Arabidopsis (Quintero and Blatt, 1997). Since then, many KUP members have been reported in various flowering plants, such as Oryza sativa (Gupta et al, 2008), Zea mays (Zhang et al, 2012), Triticum aestivum (Cheng et al, 2018), Solanum lycopersicum (Hyun et al, 2014), Populus trichocarpa (He et al, 2012), Prunus persica (Song et al, 2015), Cicer arietinum (Azeem et al, 2018), Nicotiana tabacum (Song et al, 2019), and Manihot esculenta (Ou et al, 2018). Some KUP genes have been reported in cotton (Wang et al, 2018;Wang Y. et al, 2019).…”
Section: Introductionmentioning
confidence: 99%